Glare from LED illuminants of different colour temperature under simulated driving conditions at night - Matezanz, Beatriz M. (2023)
LED technology is becoming increasingly prevalent in our daily lives, including on the roads at night, in the form of street lights and car headlights. Previous studies have shown that LEDs with a high correlated colour temperature can cause more discomfort glare than LEDs with a low correlated colour temperature. However, it is not yet known how this parameter affects disability glare in drivers under mesopic conditions. The main objective of this study is to analyse the influence of the spectral emission of lamps on glare during a representative night-driving task, specifically the reaction time.Twenty young subjects participated in the study. A two-channel Maxwellian optical vision system was used to measure foveal reaction time without and with a glare presented at a temporal retinal eccentricity of 10°. A 2º stimulus with a Weber contrast of 0.1 was used, presented over a background field with two different luminances, 0.1 and 1 cd/m2, provided by a LED lamp with a correlated colour temperature of 4000 K. Glare source was produced by two LED with correlated colour temperature of 2800 and 6500 K, providing an illuminance of 50 lux. In the glare condition, reaction time is significantly lower for the background luminance of 1 cd/m2 respect to 0.1 cd/m2, for both 2800 K (p < 0.05) and 6500 K (p < 0.05) lamps. No effect of correlated colour temperature is found on reaction time measurement for 1 cd/m2 (p =0.23). In conclusión, our study found that young drivers experience similar glare impairment measured in terms of visual reaction time regardless of the colour temperature of the LED light source.